Sealing ability of white and gray mineral trioxide aggregate mixed with distilled water and 0.12% chlorhexidine gluconate as a root end filling material: An ex vivo evaluation - Sreegowri; K Harish Kumar Shetty; M S Prathap; K J Prithviraj (Wolters Kluwer Medknow Publications, 2013)
Aim: The aim of this study was to evaluate the sealing ability of white and gray mineral trioxide aggregate (MTA) mixed with distilled water and 0.12% chlorhexidine (CHX) gluconate when used as a root-end filling material using the dye-penetration technique. Materials and Methods: A total of 48 single-rooted human teeth were cleaned, shaped, and obturated with gutta-percha and AH Plus sealer. The apical 3 mm of each root was resected, and 3-mm deep root-end cavity preparations were made. The teeth were randomly divided into 4 experimental groups, each containing 8 teeth, and 2 negative and positive control groups, each containing 8 teeth. Root-end cavities in the experimental groups were filled with the experimental materials. After application of nail polish, the teeth were exposed to India ink for 72 h and longitudinally sectioned, and the extent of dye penetration was measured with a stereomicroscope. Results : No statistically significant differences were observed in the sealing ability of gray and white MTA mixed with distilled water and 0.12% CHX. Conclusion : CHX appears to be a good alternative to replace distilled water, as a solution to be mixed with MTA.